Upamiętnianie zagłady Sinti i Romów przed i po zjednoczeniu Niemiec – wstęp do problematyki - Popieliński, Paweł; Krzyżanowski, Piotr Jacek (Rocznik Polsko-Niemiecki, 2020)
The authors of this article focus on showing the genesis of the situation and the attitude towards Sinti and Roma in the Third Reich and post-war Germany. They deal with the issue of commemorating the persecution and genocide of this community in post-war and reunified Germany. The article also indicates a selection of some of the most important memorial sites in Germany dedicated to Sinti and Roma. The genocide of Sinti and Roma represents an important turning point in their history. In line with the racist policy of the Third Reich, they were outlawed and sentenced to extermination. The subject of the Sinti and Roma extermination was long absent in the public discourse of post-war Germany and in the consciousness of society. While the Federal Republic of Germany recognised the Jewish victims fairly quickly, the Sinti and Roma genocide was ignored. The official version of the narrative stated that Sinti and Roma were persecuted in Nazi Germany not because of racist policies but because of social maladjustment (Asoziale). It was only in the 1980s that places devoted to the persecution and extermination of Sinti and Roma began to be commemorated. The present memory of the victims and the recognition of the rights of Sinti and Roma in Germany are the result of their ethnic mobilisation and long and hard-won campaigns for equal participation in society. Today, the commemoration of the wrongs suffered by Sinti and Roma during the Nazi regime is an important step for German society in dealing with its past.